THE POTENTIAL OF CASH WAQF LINKED SUKUK FOR UMKM EMPOWERMENT - Nurjannah, Mauliya Redyan; Rahmat, Rahmat (Universitas Siliwangi, 2025)
Introduction to The Problem: Indonesia, the world's largest Muslim-majority country, was named the most generous country globally by the Charities Aid Foundation (CAF) for the seventh consecutive year based on the Word Giving Index 2024. The country has several Islamic public finance instruments, including zakat, infaq, sadaqah and waqf. In 2021, the Directorate of Zakat and Waqf Empowerment noted that the potential of national cash waqf reached 180 trillion rupiah. However, this huge potential has not been optimally managed, while the welfare of the Muslim community and access to financing for MSMEs remain a challenge.Purpose/Objective Study: This research aims to identify the potential of Cash Waqf Linked Sukuk (CWLS) for MSMEs empowerment.Design/Methodology/Approach: This research used a qualitative approach to provide a detailed description in the discussion section, making it easier for readers to understand. The data used is secondary data obtained from previous research results or journals that have been published via the internet, and statistical data sourced from OJK.Findings: This study finds that CWLS has a great opportunity in Indonesia. The legality of cash waqf supports this stated in the law as well as cooperation between the Indonesian Waqf Board, Islamic financial institutions, Bank Indonesia, the Ministry of Finance, and the Ministry of Religious Affairs. Good management can maximize the potential of CWLS for MSME empowerment. Recommendations for further research include the development of a CWLS-based MSME empowerment model that utilizes big data and artificial intelligence, enabling in-depth analysis to understand the specific needs of MSMEs and optimize fund allocation.Research Type: Research Article